Hubungan faktor individu dan akauntabiliti dengan pemindahan latihan perguruan dalam kalangan guru siswazah - Abdul Rahim, Haslina; Zainal Abiddin, Norhasni (Pusat Pengembangan dan Publikasi Karya Ilmiah (P3KI) Sekolah Pascasarjana, Universitas Pendidikan Indonesia, 2014)
Individual factors and accountability is an important role in influencing the transfer of teacher training. Therefore, teachers must have the particular individual characteristics and responsible for the training received to be applied to the school to improve job performance and student achievement. This study examines the relationship of individual factors and accountability in training transfer among graduate teachers. The questionnaire was distributed to a sample of 207 graduate teachers from 38 primary schools in Selangor, Malaysia. The results showed that transfer of training occurs among these teachers. In addition, the study found a significant positive relationship between individual factors and accountability to the transfer of training.